2019
DOI: 10.31297/hkju.19.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Financing Municipal Tasks in Slovenia

Abstract: The paper examines whether the system implemented for financing local communities (municipalities) in Slovenia in the period 2010-2016 is compliant with the European Charter of Local Self-Government. We examined the cost coverage for performing the tasks of municipalities, the cost structure and the rate of interconnections between the budgeted funds under the eligible expenditure mechanism and the data collected on costs by municipality. Our hypothesis states that the principles whereby funding would be comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Increasing the financial capacity of local self-government also creates opportunities not only to finance basic functions, but also to invest in advanced functions, such as innovative development. This is also confirmed by research of Brezovnbik et al, [12], in which they examined at the level of Slovenian municipalities the coverage of costs for the fulfilment of municipal tasks, the structure of costs and the degree of connection between budgeted incomes and expenditures of municipalities. Their analysis showed that in the observed time period 2010-2016, the incomes intended for the provision of individual competencies exceeded the expenses associated with the provision of these competencies.…”
Section: Introductionsupporting
confidence: 64%
“…Increasing the financial capacity of local self-government also creates opportunities not only to finance basic functions, but also to invest in advanced functions, such as innovative development. This is also confirmed by research of Brezovnbik et al, [12], in which they examined at the level of Slovenian municipalities the coverage of costs for the fulfilment of municipal tasks, the structure of costs and the degree of connection between budgeted incomes and expenditures of municipalities. Their analysis showed that in the observed time period 2010-2016, the incomes intended for the provision of individual competencies exceeded the expenses associated with the provision of these competencies.…”
Section: Introductionsupporting
confidence: 64%